2019
DOI: 10.3389/fmicb.2019.02577
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Serotype, Genotype, and Antibiotic Susceptibility of Salmonella Prevalent in Pickled Ready-to-Eat Meat

Abstract: Pickled ready-to-eat meat (PRTEM) is a meat product that is treated with various seasonings and then cooked. PRTEM is a popular food consumed mostly in China and some Asian countries. Since this food is considered ‘ready to eat’, once it is contaminated by foodborne pathogens such as Salmonella, the prospect for significant morbidity, mortality, and immeasurable economic losses can occur. Here we investigated the prevalence and concentration of Salmonella in 107 PRTEM samples collected from Shaanxi, China duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…All bla CTX-M-55 -positive ESBL-SE isolates were subtyped by PFGE following digestion with Xba I (TaKaRa, Dalian, China) according to the Centers for Disease Control and Prevention (CDC) protocols [ 32 ]. The digested DNA fragments were separated by a CHEF Mapper electrophoresis system (Bio-Rad Laboratories, Hercules, CA, USA) as previously described [ 33 ]. S. enterica serovar Braenderup H9812 was used as the standard control.…”
Section: Methodsmentioning
confidence: 99%
“…All bla CTX-M-55 -positive ESBL-SE isolates were subtyped by PFGE following digestion with Xba I (TaKaRa, Dalian, China) according to the Centers for Disease Control and Prevention (CDC) protocols [ 32 ]. The digested DNA fragments were separated by a CHEF Mapper electrophoresis system (Bio-Rad Laboratories, Hercules, CA, USA) as previously described [ 33 ]. S. enterica serovar Braenderup H9812 was used as the standard control.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, Salmonella was isolated from 128 out of 657 (19.5%) examined poultry farms in the period from 2014 to 2018, and these results were nearly [18,23] found Salmonella in low percentage, about 7% and 7.1%, respectively, in samples isolated from poultry farms in Egypt. Moreover, El-Sharkawy et al [24] isolated Salmonella in high percentage (41%) from poultry farms in Egypt; also, Salmonella was isolated from poultry farms in Brazil and USA in high percentage, about 37% and 56%, respectively [25,26]. In our study, in the period from 2014 to 2018, all positive samples for Salmonella were examined for antibiotic resistance against 10 different antibiotics which showed that the highest average percentage of resistance was with penicillin and ampicillin followed by tetracycline, nalidixic acid, trimethoprim, [23] recorded that most of the tested Salmonella serovars were multidrug resistant and had high MAR indicated against the commonly used antibiotics in the poultry industry in Egypt.…”
Section: Salmonella Species Isolatesmentioning
confidence: 99%
“…Moreover, Hassan et al [27] revealed that Salmonella isolates showed complete resistance against penicillin, while they were highly resistant to nalidixic acid (80.8%), sulphamethoxazole/trimethoprim Veterinary Medicine International (76.9%), ampicillin (69.2%), and oxytetracycline (65.4%), while Eguale [28] reported that 42.3% were resistant to ampicillin and chloramphenicol, while 30.9%, 19%, 7.7%, and 3.9% were resistant to tetracycline, nalidixic acid, ciprofloxacin, and trimethoprim for Salmonella isolated from broilers in Ethiopia. In contrast, Wang et al [26], in USA, mentioned the rates of isolates resistant to ciprofloxacin and tetracycline (100%), then chloramphenicol (99%), ampicillin (97%), and trimethoprim-sulfamethoxazole (97%). [20] found Staphylococcus species in 24.75% of examined chicken farms.…”
Section: Salmonella Species Isolatesmentioning
confidence: 99%
“…Typically, Gram-negative bacteria produce β-lactamases, such as TEM enzymes, that hydrolyze drugs, such as penicillin and older cephalosporins, resulting in resistance to β-lactam antibiotics [ 8 ]. Fluoroquinolone resistance is associated with specific point mutations within the quinolone resistance-determining regions (QRDRs) of DNA gyrase ( gyrA ), leading to not only target alterations that reduce the binding affinity of the drugs but also the presence of plasmid-mediated quinolone resistance (PMQR) encoding genes of the qnr alleles [ 9 ]. These acquired antimicrobial resistance determinants are public health hazards because plasmids whose genes encode antibiotic resistance can expand such resistance through horizontal transmission [ 10 ].…”
Section: Introductionmentioning
confidence: 99%